The role of government and the international competitiveness of SMEs: Evidence from Ghanaian non-traditional exports. Issue 4 (7th October 2019) - Appiah, Kenneth; Osei, Collins; Selassie, Habte; Osabutey, Ellis
Abstract : Purpose: The nature of international markets and the challenges with respect to the competitiveness of small- and medium-sized enterprises (SMEs) makes it imperative to examine government support. This study aims to assess the role and effectiveness of government and the export promotion agencies in supporting exports by non-traditional horticultural SMEs in Ghana. Design/methodology/approach: The study used a qualitative research design, which involved semi-structured interviews with senior managers of six export facilitating institutions to gain an understanding of the services offered to SMEs with respect to exports of non-traditional horticultural products. Findings: The findings reveal inadequate cost-efficient sources of non-traditional horticultural export financing for SMEs. This is a hindrance to the international competitiveness of exporting SMEs in developing countries such as Ghana. In addition, effective and coordinated support from export promotion agencies was found to be critical. Originality/value: The study highlights the importance of government's role in policymaking and implementation of export-led programmes for horticultural exporting firms in Ghana. Despite their strategic importance, this area of research has not attracted the attention of researchers, with little or no information on the horticultural international competitiveness of non-traditional horticultural products.